2013
DOI: 10.1016/j.brat.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing recovery rates: Lessons from year one of IAPT

Abstract: BackgroundThe English Improving Access to Psychological Therapies (IAPT) initiative aims to make evidence-based psychological therapies for depression and anxiety disorder more widely available in the National Health Service (NHS). 32 IAPT services based on a stepped care model were established in the first year of the programme. We report on the reliable recovery rates achieved by patients treated in the services and identify predictors of recovery at patient level, service level, and as a function of complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
347
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(393 citation statements)
references
References 10 publications
24
347
2
8
Order By: Relevance
“…Comparison of the results with those of practice-based studies in routine service settings is more complicated, because the recovery rates depend upon how the sample is chosen (Barkham et al, 2012). However, the present outcome results exceeded those of the selected completers' group in practice-based studies, where 40-58% had recovered (Richards & Borglin 2011, Gyani et al, 2013, Holmqvist et al, 2014.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Comparison of the results with those of practice-based studies in routine service settings is more complicated, because the recovery rates depend upon how the sample is chosen (Barkham et al, 2012). However, the present outcome results exceeded those of the selected completers' group in practice-based studies, where 40-58% had recovered (Richards & Borglin 2011, Gyani et al, 2013, Holmqvist et al, 2014.…”
Section: Discussionmentioning
confidence: 51%
“…Practice-based studies in routine service settings have similarly shown short-term psychotherapeutic treatment to be effective, with 40-58% of the patients who completed the treatment recovering (Gyani et al, 2013;Holmqvist et al, 2014;Richards & Borglin 2011, Stulz et al, 2013. Systematic studies of the ideal dosage of short-term psychotherapy for gaining the optimal outcome are rare, however.…”
Section: Is Interpersonal Counselling (Ipc) Sufficient Treatment Formentioning
confidence: 99%
“…Stepping up and down aims to ensure the seamless transition of patients to and from Primary and Secondary Care services (CSIP, 2008). Although the exact configurations of IAPT services differ (Gyani, Shafron, Layard, & Clark, 2013), many have extended the range of therapies to patients with anxiety and depression into both Primary and…”
Section: Introductionmentioning
confidence: 99%
“…[5] Another major effort to disseminate and implement EBPs underway in the United Kingdom (Improving Access to Psychological Therapies) has also achieved significant clinical and training outcomes. [6] …”
Section: National Dissemination and Implementation Of Evidence-basedmentioning
confidence: 99%